Cultura de doação: cenários possíveis pelo Design Estratégico - Ramos, Cristiane Correa (Universidade do Vale do Rio dos Sinos, 2023)
The donation culture seeks to work on the core cause to extinguish structural problems in our society to generate social development. It can be seen as a means to foster a more humane culture of care or as an end that not only acts against inequities but also changes mindsets. The main objective of this article was to propose future scenarios that contribute to promoting the culture of donation in Brazil. For the development of this social research, was applied a qualitative method of an exploratory nature, guided by the methodology of strategic design constituted by a bibliographical research that aimed to understand how the construction of scenarios can be interpreted from the perspective of strategic design, by a bibliographical research and documentary to identify how a society expresses the ability to take care of itself in the face of the phenomenon of social inequality, through an online workshop with different actors who contributed to the development of the proposition of a future scenario to foster the culture of donation in Brazil. The research results indicate the need to create new habits so that, through behavioral change, people exercise citizenship through collaborative participation. In this way, it could be possible to build and strengthen cultural elements to establish donations in our culture, that is, to make donations natural in our daily lives, both in the corporate sphere and in society. It is necessary to act in a constellation of actions: education and information, awareness and technology. As support, to welcome the constellation of activities, a scenario is pointed out aiming to work from the global to the local and in an open, small, and connected way. Thus, it will be possible to visualize the changes occurring around people in their neighborhoods, providing a solution where the community can deal with its problems.
Keywords: Cultura de doação; Design estratégico; Cenários futuros; Cenário PLAC; Giving culture; Strategic design; Future scenarios; Scenario PLAC; ACCNPQ::Ciências Sociais Aplicadas::Desenho Industrial